Comparison of cefotetan and cefoxitin as prophylaxis in cesarean section - Varner, M W; Weiner, C P; Petzold, C R; Galask, R P (American journal of obstetrics and gynecology, 1986)
A study comparing the efficacy of cefotetan versus cefoxitin for prophylaxis in patients undergoing cesarean section was carried out at the University of Iowa. After institutional review, 36 subjects who met the study criteria and agreed to participate were entered into the study; of these, 29 were evaluable for efficacy. Twenty subjects received a single 2 gm dose of cefotetan, and nine subjects received three 2 gm doses each of cefoxitin. Both antibiotics were administered intravenously at the time the umbilical cord was clamped. The subsequent doses of cefoxitin were given intravenously at four and eight hours after the initial dose. Clinical and bacteriologic responses were evaluated; there were no statistically significant differences between the two groups, and both antibiotics provided effective prophylaxis against infection. It appears that cefotetan is a satisfactory antibiotic choice for cesarean section prophylaxis. Further, in this small study it appears that a single dose of cefotetan is as effective as three doses of cefoxitin. This implies that cefotetan would not only decrease administration time and supplies but would decrease the cost to the patient while maintaining very acceptable infection rates.